PENYELESAIAN GUGATAN PEMBATALAN KEPUTUSAN BUPATI DELI SERDANG TERKAIT PENGANGKATAN KEPALA DESA DALAM SENGKETA PEMILIHAN KEPALA DESA - Tika Puspita Sari; Mirza Nasution; Eka Nam Sihombing (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2024)
Abstract: Village Head Election (Pilkades) is an event in a democratic party at the village level as village autonomy/village rights to elect new leaders from the village community. The village head election in Cinta Damai Village was in conflict over the results of a very narrow vote dispute, a difference of 9 votes which was marked by various frauds, resulting in dissatisfaction with the results of the village head election, the losing party felt they had been disadvantaged by the results obtained, but the problem is that the Regent of Deli Serdang still inaugurated with the Decree of the Regent of Deli Serdang Number 395 of 2022 concerning the ratification and appointment of the Head of Cinta Damai Village, Percut Sei Tuan District dated May 18, 2022 on behalf of Josta Josevina Tambunan. The purpose of this study was to determine and analyze the settlement of the lawsuit for the cancellation of the Deli Serdang Regent's Decree against the appointment of the Head of Cinta Damai Village, the results of the analysis of the judge's decision regarding the judge's considerations in resolving the dispute over the election of the Head of Cinta Damai Village, and the validity of the judge's decision regarding the cancellation of the Deli Serdang Regent's Decree concerning the Appointment of the Head of Cinta Damai Village. Based on this research, the results obtained are that dispute resolution is carried out through the State Administrative Dispute Resolution process according to Law Number 5 of 1986 by submitting files to the PTUN, PTUN to PK as a form of lawsuit to revoke the Decree of the Regent of Deli Serdang in determining the election of the head of Cinta Damai Village. Keywords: Lawsuit, Settlement, Decision, Head of Love Peace Village Abstrak: Pemilihan Kepala Desa (Pilkades) adalah suatu acara dalam pesta demokrasi di tingkat desa sebagai otonomi desa/hak desa untuk memilih pemimpin baru yang berasal dari masyarakat desa. Pemilihan kepala desa di Desa Cinta Damai terjadi konflik atas hasil perselisihan suara yang sangat tipis, berselisih 9 suara yang diwarnai berbagai kecurangan, sehingga terjadi ketidakpuasan atas hasil pilkades, pihak yang kalah merasa telah dirugikan dengan hasil yang diperoleh, namun yang menjadi masalah Bupati Deli Serdang tetap melantik dengan Keputusan Bupati Deli Serdang Nomor 395 Tahun 2022 tentang pengesahan dan pengangkatan Kepala Desa Cinta Damai, Kecamatan Percut Sei Tuan tanggal 18 Mei 2022 atas nama Josta Josevina Tambunan. Tujuan penelitian ini untuk mengetahui dan menganalisis penyelesaian gugatan pembatalan Keputusan Bupati Deli Serdang terhadap pengangkatan Kepala Desa Cinta Damai, hasil analisis putusan hakim terhadap pertimbangan hakim dalam menyelesaikan sengketa pemilihan Kepala Desa Cinta Damai, serta keberlakuan putusan hakim terhadap pembatalan Keputusan Bupati Deli Serdang tentang Pengangkatan Kepala Desa Cinta Damai. Berdasarkan penelitian ini diperoleh hasil bahwa penyelesaian sengketa dilakukan melalui proses penyelesaian Sengketa Tata Usaha Negara menurut Undang-Undang Nomor 5 Tahun 1986 dengan melimpahkan berkas ke PTUN, PTUN samapai PK sebagai bentuk gugatan pencabutan SK Bupati Deli Serdang dalam penetapan pemilihan kepala Desa Cinta Damai. Kata kunci: Gugatan, Penyelesaian, Keputusan, Kepala Desa Cinta Damai